Black Hole Mass Estimation in Type 1 AGN: Hβ vs. Mg II Lines and the Role of Balmer Continuum - Kovačević-Dojčinović, Jelena; Marčeta-Mandić, Sladjana; Popović, Luka Č. (Frontiers in Astronomy and Space Sciences, 2017)
Here we investigate the Hβ and Mg II spectral line parameters used for the black hole mass (MBH) estimation for a sample of Type 1 Active Galactic Nuclei (AGN) spectra selected from the Sloan Digital Sky Survey (SDSS) database. We have analyzed and compared the virialization of the Hβ and Mg II emission lines, and found that the Hβ line is more confident virial estimator than Mg II. We have investigated the influence of the Balmer continuum emission to the MBH estimation from the UV parameters, and found that the Balmer continuum emission can contribute to the overestimation of the MBH on average for ~ 5% (up to 10%).